Neuropsychological dimension of schizophrenia - evaluation possibilities and therapeutic implications - Makarewicz, Agata; Karakuła-Juchnowicz, Hanna; Łobejko, Łukasz (Current Problems of Psychiatry, 2017)
Introduction: In the last decades, researchers' attention has been focused on cognitive dysfunction in schizophrenia. Numerous studies indicate the existence of neurodegenerative deficits in schizophrenia including, but not limited to, motor functions, learning and memory, executive functions, attention, language, spatial skills and general intelligence.Method: A review of available literature on the topic of the past two decades, available in the Pubmed, EBSCO, SCOPUS databases has been made using the keywords: schizophrenia, cognition, early intervention.Results: Cognitive dysfunction is an important feature of the prodromal phase and the first episode of schizophrenia. Researchers have thus proposed to initiate early therapeutic interventions for people with so-called risky mental conditions. The article includes the reference to research on neurocognitive disorders essence in schizophrenia, the definition and review of methods used to identify specific cognitive deficits and issues related to risk of developing psychosis and early therapeutic intervention in high-risk states.Conclusions: Researchers report the importance of detecting cognitive disorders in the early stages of schizophrenia. This broad-ens the range of therapeutic interventions and enables early intervention in the increased risk of psychosis.